A critical analysis of neoliberal mechanisms in the UAE: the mistreatment of migrant workers in an autocratic state - Akhtar, Sakib (2022)
The United Arab Emirates (UAE) economic growth and development have largely been driven by migrant labour. Approximately 95% of the workforce in the UAE is comprised of them (Sonmez et al., 2011). Nevertheless, they are frequently the ones to experience the negative effects of the autocratic neoliberal policies soaked in the social systems. For instance, the kafala (sponsorship) system, a crucial tool for immobilising migrant workers and making it difficult for them to freely sell their skills on the job market, hasn't been seen through the prism of neoliberalism. While there is currently literature available about neoliberalism in North America and Europe. Despite their importance, we know very little about how neoliberal policies affect migrant workers in the Global South, including the UAE. Here, we employed a strategy based on secondary qualitative data, including focus group discussions and information on the living and working conditions of migrant workers in the UAE. With the wide-ranging situations that this approach revealed, we concentrated on working conditions, contracts, pay, living conditions, challenges, and suggested solutions for our study. Three mechanisms— the kafala system, anti-worker collectivisation, and attacking the resistive capacity of unions—were identified in light of these findings. Our study highlights the current capabilities of neoliberalism and its forms as used by autocratic power, we further substantiate that these mechanisms interplay and overlap to increase the vulnerability of migrant workers. This analysis is crucial because it suggests possible directions for future research. For instance, a comparison of the treatment of migrant workers under neoliberal policies in the democratic United States and the autocratic United Arab Emirates.